Pra-Islam dan Bahasa Arab: Bahasa dan Sastra Sebelum Munculnya Islam: Pre-Islam and Arabic: Language and Literature Before the Rise of Islam - Chamdar Nur; Andi Abdul Hamzah (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2025)
This research examines the development of Arabic language and literature before the arrival of Islam, with a focus on the Jahiliyah era. This study covers the characteristics and variations of pre-Islamic Arabic, Jahiliyah poetry, the role of oral traditions, as well as famous poets such as Nabighah al-Dhubyani and Imru' al-Qais. Further discussion concerns the influence of socio-economic conditions on literary development at that time. This article also refers to the arguments of the Koran, hadith, as well as the views of ulama on this topic. This research uses a qualitative approach with descriptive analysis methods. The data used comes from primary and secondary sources, including Jahiliyah poetry, classical books, and the views of scholars on pre-Islamic Arabic language and literature. This research combines a historical linguistic approach and a sociocultural approach. A linguistic approach is used to analyze dialect variations and characteristics of pre-Islamic Arabic. The themes of Jahiliyah poetry, such as love, war, and praise of the tribe, reflect the social life of pre-Islamic Arab society. The structure of the poem, with its beautiful use of rhetoric and metaphor, shows the linguistic richness of the Arabic language passed down to the Islamic era. Jahiliyah poetry, such as the works of Imru' al-Qais and Nabighah al-Dhubyani, is not only historical documentation but also provides insight into the social, economic and cultural dynamics that shaped Arab society.